Customer service quality in B2B market from the buyer´s perspective - Vlčková, Vladimíra; Podškubková, Lucie (VGTU Publishing House Technika, 2018)
The importance of services for companies is significant and still increasing. Customers expect fulfilment of their requirements concerning not only the product, but also the quality of services relating to this product. The core of competitiveness is thus moving from the product itself to the supplier abilities created by the entire supply system with a dynamic structure. Therefore, it is necessary to understand the specific needs of each single customer concerning services within the entire supply system. On the basis of a comparison of the outcomes of a targeted literature review and an analysis of evaluation of the service quality by the customers purchasing products of a selected company, the paper identifies the deciding parameters and methods of customer service quality assessment in the B2B market from the buyer’s perspective.
Kvalita služeb zákazníkům na B2B trhu z pohledu odběratele
Keywords: customer service; service quality; parameters of service quality; service quality assessment; B2B market; služby zákazníkům; kvalita služeb zákazníkům; parametry kvality sluežb zákazníkům; hodnocení kvality služeb zákazníkům; B2B trh